Tourism education global issues and trends - Sheldon, Pauline J.; Hsu, Cathy H. C. (Tourism social science series ;, 2015)
This book explores the changing landscape of tourism education in the global context. It examines and seeks to provide answers to three main questions: What knowledge and skills should tourism students be exposed to? How should tourism education programs at all levels be designed to create responsible leaders for the future of tourism? What is the employability and range of careers students can expect after graduation? The book will also delve into the issues related to curriculum design and pedagogical innovation in some detail including technological innovation. It will explore new possibilities in alternative disciplinary approaches to the study of tourism, theoretical concepts in tourism education, cross-disciplinarity, multi-disciplinarity, inter-disciplinarity and trans-disciplinarity. The challenges of institutional rigidity in different national contexts will be explored as well as tourism education in the developing world.